In-situ fabrication of yttria dispersed copper alloys through MA-HIP process - B. Huang; Y. Hishinuma; H. Noto; R. Kasada; N. Oono; S. Ukai; T. Muroga (Nuclear Materials and Energy, 2018)
Yttria (Y2O3) dispersed copper alloys were fabricated by an in-situ process combining Mechanical Alloying (MA) and Hot Isostatic Pressing (HIP). In this process, CuO powder was added into Cu(Y) alloy powders halfway during mechanical alloying (MA). To investigate the effects of Y + CuO amount on the MA process and HIP process respectively, four kinds of samples (Cu-0/1/3/5wt%Y2O3) were studied in this research. For powders after MA, it was confirmed by an X-ray diffraction system (XRD) that more Y + CuO addition can refine the grain size. By calculating the lattice parameters from the XRD data, and analyzing the thermal dynamics data that were obtained from the TG-DTA tests, it can be concluded that the Cu, Y were alloyed successfully at first, and then after the CuO addition, reaction between Cu(Y) and CuO occurred, extracting part of Y solute from the Cu(Y) solution. Consequently, the alloying and grain refinement effect together enhance the microhardness of the powders. After consolidation by HIP, the formation of Y2O3 particles were confirmed by XRD. The relative density and the Vickers hardness of the HIP samples increased with the increasing Y2O3 amounts, whereas the electrical conductivity showed an opposite change tendency. Keywords: Copper alloy, Dispersion strengthening, Copper oxide, Mechanical alloying, Hot isostatic pressing